Pengembangan Tes Miskonsepsi Ranah Kognitif pada Materi Suhu dan Kalor - Muslimah, Laila Siti Muslimah; Mulvia, Rahmadhani; Warliani, Resti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to develop a valid and reliable diagnostic misconception test instrument on the topic of heat and temperature based on Kahoot. Using the Research and Development (R&D) approach with a modified 4D model (Define, Design, Develop, and Disseminate—limited to the Develop stage), the instrument was designed as a four-tier test comprising answers, confidence levels, reasons, and confidence in reasons. The subjects were eleventh-grade science students in Garut Regency who had studied heat and temperature. The results indicated high validity and reliability, with a Cronbach’s Alpha coefficient in the high category. The difficulty index showed 25% easy, 60% moderate, and 15% difficult items, while most discrimination indices were good. The instrument effectively identified misconceptions, revealing that 31.82% of students experienced misconceptions, 50% lacked understanding, and 18.18% had correct conceptual understanding. Overall, the Kahoot-based four-tier diagnostic test proved effective for detecting misconceptions and can serve as a practical tool for teachers to design targeted instruction and remediation in physics learning.